Portugal : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper describes financial conditions and growth at risk in Portugal. The macro-finance literature and recent experience provide compelling evidence that financial imbalances grow in good times, creating downside risks to economic growth. The analysis highlights the importance of the price of risk, leverage and credit growth as leading indicators of risks to gross domestic product growth. The price of risk appears to provide the most powerful signal in the short term, while credit aggregates are the most significant predictor in the medium term. This finding is consistent with the volatility paradox and is line with other empirical studies. The Growth-at-Risk (GaR) model suggests contained downside risks to Portugal's growth projections at the current juncture based on financial conditions data, but credit growth should continue to be monitored given still high leverage. The moderate risk to growth identified by the GaR model reflects the impact of low credit spreads and volatility in the financial markets, in their turn reflecting the prevailing policy mix. Still, a repricing of risks and other shocks could be magnified by the still-high leverage, and lead to less favorable growth outcomes.